2014
DOI: 10.1152/jn.00320.2014
|View full text |Cite
|
Sign up to set email alerts
|

Subtype-dependent postnatal development of direction- and orientation-selective retinal ganglion cells in mice

Abstract: Chen H, Liu X, Tian N. Subtype-dependent postnatal development of direction-and orientation-selective retinal ganglion cells in mice. J Neurophysiol 112: 2092J Neurophysiol 112: -2101J Neurophysiol 112: , 2014. First published August 6, 2014; doi:10.1152/jn.00320.2014.-The direction-selective ganglion cells (DSGCs) and orientation-selective ganglion cells (OSGCs) encode the directional and the orientational information of a moving object, respectively. It is unclear how DSGCs and OSGCs mature in the mouse re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 43 publications
7
27
0
Order By: Relevance
“…We found no significant difference for the DSIs of either ON and ON-OFF DSGCs across conditions [3,6], and a small but significant increase in the vector sum for ON-OFF DSGCs across development, as described previously [5,8], suggesting a visually-driven maturation …”
Section: Author Manuscriptsupporting
confidence: 77%
See 2 more Smart Citations
“…We found no significant difference for the DSIs of either ON and ON-OFF DSGCs across conditions [3,6], and a small but significant increase in the vector sum for ON-OFF DSGCs across development, as described previously [5,8], suggesting a visually-driven maturation …”
Section: Author Manuscriptsupporting
confidence: 77%
“…We found no significant difference for the DSIs of either ON and ON-OFF DSGCs across conditions [3,6], and a small but significant increase in the vector sum for ON-OFF DSGCs across development, as described previously [5,8], suggesting a visually-driven maturation of tuning properties. Though DSGCs were strongly tuned at eye-opening and after darkrearing, both ON and ON-OFF DSGCs in young and dark-reared mice retained the immature distribution of preferred directions, failing to cluster along the cardinal axes ( Figure 2; Figure S2).…”
Section: Clustering Of Dsgc Preferred Directions Along Cardinal Axes supporting
confidence: 76%
See 1 more Smart Citation
“…1C-F ). Recordings were conducted in the ventral retina, where there is a higher concentration of S-cones versus M-cones due to the gradient distribution of opsins in the mouse retina (Wang et al, 2011;Baden et al, 2013;Hoon et al, 2014) (Fig. 1C).…”
Section: Methodsmentioning
confidence: 99%
“…In Gnat1 Ϫ/Ϫ mice, visible light evoked responses only at the highest light intensities, indicating activation of M-cones that are present at a lower density in ventral than dorsal retina (Wang et al, 2011;Baden et al, 2013). This was verified as being an M-cone-mediated response by obtaining a similar response threshold after sustained exposure of WT retinas to green light generated by placing a green filter over the microscope condenser (ϳ1.6 ϫ 10 6 R*/rod/s for at least 2 min as used in Wang et al, 2011; data not shown).…”
Section: Methodsmentioning
confidence: 99%